2017
DOI: 10.1002/jssc.201700424
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fabrication strategy on the enantioseparation performance of β‐cyclodextrin‐functionalized polymethacrylate monoliths: A comparative evaluation

Abstract: To evaluate the effect of the preparation strategy on the enantioseparation performance of β-cyclodextrin-functionalized monoliths, a series of β-cyclodextrin-functionalized organic polymeric monolithic columns were prepared through two-step, single-step, and one-pot approaches, using the same cyclodextrin, linker-spacer, and crosslinker. Physicochemical characterization of the columns was carried out by determining the morphology, β-cyclodextrin density, permeability, and chromatographic efficiency. For each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…e polymerization of MMIP, MNIP, MIP, and NIP monoliths was conducted in situ or using the one-pot method inside microbore columns made of the silicosteel with an inner diameter of 1 mm. e method was preferred due to the following advantages: it showed a higher enantiomer resolution to separate chiral compounds, faster synthesis than other polymerization methods, provided reasonable control to achieve desired characteristics of the monolith through optimization of chemical and physical parameters, and was easy to perform [28]. A microbore monolith column (1 mm i.d) was used for its easiness to be paired with the HPLC system without modification as compared to the capillary column, and small quantities of enantiomer samples were also another advantage.…”
Section: Resultsmentioning
confidence: 99%
“…e polymerization of MMIP, MNIP, MIP, and NIP monoliths was conducted in situ or using the one-pot method inside microbore columns made of the silicosteel with an inner diameter of 1 mm. e method was preferred due to the following advantages: it showed a higher enantiomer resolution to separate chiral compounds, faster synthesis than other polymerization methods, provided reasonable control to achieve desired characteristics of the monolith through optimization of chemical and physical parameters, and was easy to perform [28]. A microbore monolith column (1 mm i.d) was used for its easiness to be paired with the HPLC system without modification as compared to the capillary column, and small quantities of enantiomer samples were also another advantage.…”
Section: Resultsmentioning
confidence: 99%
“…Methacrylate-based monolithic columns are one of the materials most prone to development. In addition to being practical, it is shown that the column can be applied sometimes without requiring any silanization pro-cess [105,106,[321][322][323] Denizli et al synthesized chiral monolithic capillary column based on butyl methacrylate in their studies in which the enantiomeric separations of including some of hydrophobic amino acids investigated, which N-Metacryloyl-L-Histidine monomer (MAH) and N-Metacryloyl-L-Glutamic Acid (MAGA) was used as chiral selectors, resptectively in CEC [324,325].…”
Section: Monolithsmentioning
confidence: 99%
“…Recently, increasing efforts have been directed toward the development of organic polymer-based chiral monolithic columns because of their excellent permeability, pH stability, low resistance to mass transfer and high performance [3][4]. So far, various chiral selectors functionalized polymer-based chiral monoliths have been reported, such as cyclodextrin and its derivatives [5][6], quinidine and its derivatives [7][8][9], cellulose derivatives [10], proteins [11,12], macrocyclic antibiotics [13][14], crown ethers [15] and chiral ion-exchangers [16].…”
Section: Introductionmentioning
confidence: 99%